Product diversification and labor productivity dispersion in German manufacturing industries - René Söllner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
Empirical research has shown tremendous productivity differences, even within narrowly defined industries. A great host of studies is explainsing this productivity disparity by factors such as idiosyncratic technology shocks, input price differences, management skills, or international trade. Although these explanations are undoubtedly important, the current paper suggests that product diversification strategies of firms can also play an important role. Using a matched producer-product panel dataset of German manufacturing industries over the period 2003-2006, we find that the average degree of product diversification across industry establishments is positively related to within-industry labor productivity dispersion.
Keywords: L11; L22; L25; 330; Product Diversification; Productivity; Industrial Dynamics; Diversifikation; Produktivität; Verarbeitendes Gewerbe; Deutschland